Rapid and sustained cognitive recovery in APP/PS1 transgenic mice by co-administration of EPPS and donepezil - Kim, Hye Yun (Sci Rep, 2016)
Alzheimer’s disease (AD) is a neurodegenerative disease characterized by sequential progression of pathological events, such as aggregation of amyloid-β proteins, followed by outward symptoms of cognitive impairments. Given that a combination of different therapeutic strategies often provides more rapid and effective outcomes in diverse areas of clinical treatment, we hypothesized that administration of anti-amyloid drugs with cognitive enhancers would result in synergistic effects in AD treatment. Here, we co-administered 4-(2-hydroxyethyl)-1-piperazinepropane-sulphonic acid (EPPS), an amyloid-clearing chemical, and donepezil, an acetylcholinesterase inhibitor, to determine whether they could serve complementary roles for each other in regards to AD treatment. We found that oral administration of these two molecules led to a rapid and consistent cognitive improvement in APP/PS1 transgenic mice. Although there was no evidence for synergistic effects, our results indicated that EPPS and donepezil function complementary to each other without altering their individual effects. Thus, the combined use of disease-modifying and symptomatic relief drugs may be a promising approach in the treatment of AD.